1994
DOI: 10.1017/s0033291700027719
|View full text |Cite
|
Sign up to set email alerts
|

Central monitoring deficiency and schizophrenic symptoms

Abstract: SynopsisTwenty-five schizophrenic patients currently experiencing Schneiderian symptoms performed a series of tasks in which drawings had to be made in the absence of immediate visual feedback. In comparison to 10 normal controls and to 30 patients not experiencing Schneiderian symptoms, the target group had great difficulty in keeping track of their performance and remembering what actions they had made. These results are consistent with the hypothesis that Schneiderian symptoms (such as delusions of alien co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(70 citation statements)
references
References 10 publications
2
65
1
2
Order By: Relevance
“…By contrast, the same patients had no difficulty making the correction when they were provided visual feedback on the displacement of the lever (e.g. Frith and Done, 1989;Mlakar et al, 1994). The problem with this type of experiment, however, is that it mostly stresses the automatic part of the action monitoring system, but tends to overlook the conscious part of this mechanism, that which makes it possible to give an explicit judgement on the action.…”
Section: Is There a Failure Of The Action Monitoring System In Schneimentioning
confidence: 99%
“…By contrast, the same patients had no difficulty making the correction when they were provided visual feedback on the displacement of the lever (e.g. Frith and Done, 1989;Mlakar et al, 1994). The problem with this type of experiment, however, is that it mostly stresses the automatic part of the action monitoring system, but tends to overlook the conscious part of this mechanism, that which makes it possible to give an explicit judgement on the action.…”
Section: Is There a Failure Of The Action Monitoring System In Schneimentioning
confidence: 99%
“…Di¤culty with such monitoring is suggested by failure to correct simple limb movement errors in the absence of visual feedback (Frith & Done 1989). In addition, patients have di¤culty remembering their own actions when these were carried out without visual feedback (Mlakar et al 1994). In both cases these results suggest that patients' knowledge about their own actions depends more on seeing what they have done rather than knowing in advance what they will do.…”
Section: (D) Hallucinations: Misperception Of Actionmentioning
confidence: 99%
“…Mlakar et al [10] tested self-monitoring using a paradigm that involved the production and subsequent identification of drawings. The researchers argued that identification of drawings generated out-of-sight (without visual feedback) would make a heavy demand on self-monitoring, and they found that schizophrenic patients currently experiencing 'Schneiderian' symptoms made proportionately more such identification errors than non-symptomatic schizophrenic patients or non-patient controls.…”
Section: Introductionmentioning
confidence: 99%